Plan de negocios para la creación de una empresa dedicada a la comercialización de calzado formal para hombres con suelas importadas de Brasil, en la ciudad de Quito - López Villarroel, Ángel Andrés (2020)
Fashion is the best tool to help us dream. Giorgio Armani. The purpose of this project is to study and analyze the opportunity to create a company in Quito dedicated to the commercialization of casual men shoes with imported soles. The soles are imported from Brazil due to the advanced manufacturing techniques of footwear inputs, quality and competitive prices in industry. In addition, Ecuadorian consumers have good Brazilian´s products acceptance. With the purpose of creating the necessary strategies to position the company in the market, external environmental forces affecting the industry were studied in the framework in which the company will operate. The target audience is middle-high social strata male from Quito, who work and live in the north central area of the city and are receptive to digital advertising and frequent online purchases. Neuromarketing and e-commerce techniques that highlight a memorable shopping experience are emphasized, facilitating the purchase process and projecting status, self-esteem and masculinity. Trade through exclusive channels such as a physical store and a virtual store, allows to demonstrate the essence and philosophy of the brand to customers. The product will be manufactured by a high quality standard factory located in Cuenca. Shoes are made with premium leather, soles imported from Brazil and the collections are based on high-top brand designs, which makes it possible that 90.4 percent of surveyed people accepted the project. The structure of the company is a corporation which opens the opportunity to grow into a consolidated manner, integrating more investors and capital with time. The initial investment of the project is 144,837 dollars where 30 percent is self-funded and 70 percent is financed through the CFN, allowing in this way, a positive profitability with an internal return rate of 14.72 percent and a recovery period of 4 years with 7 months.